Mendesain Pembelajaran Bahasa Indonesia yang Menarik dengan Menerapkan Metode Bervariasi - Wahyuni Rahayu (Institut Dirosat Islamiyah Al-Amien Prenduan, 2022)
This study seeks to analyze and find concepts about interesting Indonesian language learning designs by applying various methods. The goal is how the teaching and learning process in Indonesian subjects can run effectively, conducive and productively. The research method used is a literature study method whose main sources are books, journals, articles, other documentation related to the topic of study. The results show that to be able to realize an attractive Indonesian language learning design is to use various (varied) learning methods, because integration between methods is important to maximize teaching materials, lead active students and reciprocal efforts. There are six methods collaborated in this research, namely lecture, demonstration, question and answer, discussion, assignment and project methods. The collaboration of these six methods in teaching and learning Indonesian makes the atmosphere more conducive, effective, efficient and productive which has an impact on the growth of interest, motivation and achievement of students.